The Power of TV: Cable Television and Women's Status in India* - Jensen, Robert; Oster, Emily (Quarterly Journal of Economics, 2009)
Cable and satellite television have spread rapidly throughout the developing world. These media sources expose viewers to new information about the outside world and other ways of life, which may affect attitudes and behaviors. This paper explores the effect of the introduction of cable television on women's status in rural India. Using a three-year, individual-level panel data set, we find that the introduction of cable television is associated with significant decreases in the reported acceptability of domestic violence toward women and son preference, as well as increases in women's autonomy and decreases in fertility. We also find suggestive evidence that exposure to cable increases school enrollment for younger children, perhaps through increased participation of women in household decision making. We argue that the results are not driven by preexisting differential trends.